Mandatory audit of small business in Malaysia: owners' perspectives - Ismail, Hashanah; Loh, Lee Boon (Conference Master Resources, 2012)
This paper reports on a survey of small businesses in Selangor and Kuala Lumpur on the perceived benefit of the statutory audit. The study finds that nearly half (44%) of the sample companies would not continue to have their accounts audited if not legally required to do so. However, the sample companies generally agreed that audit can provide a check on internal control or accounting records. The location, age, ownership structure, education level and relationship with accounting cost were the factors found to significantly affect the owners’ perception of the need for annual audit by small companies. This is the first study that uses location, education level and relationship with accounting cost as the variable to test the perceptions of business owners towards a mandatory annual audit of financial statements.